2018
DOI: 10.1590/abd1806-4841.20186527
|View full text |Cite
|
Sign up to set email alerts
|

Application of dermoscopy image analysis technique in diagnosing urethral condylomata acuminata

Abstract: BackgroundIn this study, cases with suspected urethral condylomata acuminata were examined by dermoscopy, in order to explore an effective method for clinical.ObjectiveTo study the application of dermoscopy image analysis technique in clinical diagnosis of urethral condylomata acuminata.MethodsA total of 220 suspected urethral condylomata acuminata were clinically diagnosed first with the naked eyes, and then by using dermoscopy image analysis technique. Afterwards, a comparative analysis was made for the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…However, due to the presence of thick stratum corneum on the wart surface, vessels were difficult to assess. Zhang et al . evaluated 136 cases with clinically suspected urethral warts, with dermatoscopy and dermatopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the presence of thick stratum corneum on the wart surface, vessels were difficult to assess. Zhang et al . evaluated 136 cases with clinically suspected urethral warts, with dermatoscopy and dermatopathology.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, due to the presence of thick stratum corneum on the wart surface, vessels were difficult to assess. Zhang et al 11 evaluated 136 cases with clinically suspected urethral warts, with dermatoscopy and dermatopathology. In their study, they found that the most frequent vascular features of urethral warts were punctate and polymorphic blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…[7] CA has characteristic vascular features, mainly including dotted, annular, dendritic, and hairpin vessels. [7,8] However domestic dermatologists also express dermoscopic features in regards to the lesion's appearance, such as a papillary pattern or a flat pattern. [8,9] Compared to the sensitivity of naked-eye examination (87.7%), dermoscopy improves the sensitivity of diagnosis CA (to 97.4%).…”
Section: Diagnostic Value Of Dermoscopymentioning
confidence: 99%
“…[7,8] However domestic dermatologists also express dermoscopic features in regards to the lesion's appearance, such as a papillary pattern or a flat pattern. [8,9] Compared to the sensitivity of naked-eye examination (87.7%), dermoscopy improves the sensitivity of diagnosis CA (to 97.4%). [9] Dermoscopy is a non-invasive, convenient, and efficient diagnostic technique for CA, and it can identify lesions that are invisible to the naked eye.…”
Section: Diagnostic Value Of Dermoscopymentioning
confidence: 99%
“…To the best of our knowledge, the dermoscopy of FEH has not been described before, but the patterns seen seem to be similar to those described in the case of mucosal warts/condyloma, which are also characterized by prominent polymorphic vascular patterns. [ 4 ] The lobules and septation could possibly represent the acanthosis and parakeratosis, and the multiple vessels and vascular distension visible on histopathology are reflected in the vascular patterns seen on dermoscopy.…”
mentioning
confidence: 99%